Ultrasound application in alkaline pretreatment process of spodumene to improve particle floatability - Chu, Haoran; Chen, Lanlan; Lu, Dongfang; Wang, Yuhua; Zheng, Xiayu; Zhu, Guangli (International journal of mining science and technology, 2023)
Selective surface dissolution was found to be important in spodumene flotation. In this study, we proposed to introduce ultrasound into the pretreatment process to accelerate particle vibration and cavitation, as well as the migration of mineral surface components to solution. Micro-flotation results showed that the flotation recovery of spodumene can be 86.08% by ultrasound pretreatment, but only 39.30% by traditional mechanical agitation pretreatment. Compared with traditional mechanical agitation, ultrasonic pretreatment can shorten the pretreatment process, reduce the dosage of agents, reduce the mechanical agitation speed, and improve the efficiency of the pretreating process. Inductively coupled plasma analysis showed that, in the ultrasonic system, the amount of Li, Al, and Si species in the solution was twice as much as those in the traditional preprocessing system. Moreover, the scanning electron microscope results demonstrated a larger surface dissolution area in the ultrasonic system. X-Ray photoelectron spectroscopy results showed that the atomic concentration of Si species on the spodumene surface decreased, whereas the relative atomic concentrations of Li and Al species increased, indicating that the ultrasound effect strengthened the selective dissolution of elements on the mineral surface. The high-resolution spectra of O 1s showed that more collectors are adsorbed on the mineral surface treated by ultrasonic pretreatment.